Blast Vibration Modelling - An Instrument to Optimise Quarry Production - Drew Martin (International Society of Explosives Engineers, 2012)
In March 2010 the Boral Linwood Quarry, Adelaide South Australia, implemented the blasting contractors Monte Carlo Blast Vibration Model as part of their blast design process. The Linwood Quarry was developing an area where blasting activities were marginally complying with the statutory vibration limits. Compliance to the statutory limits was only being achieved through the use of small blasts (less than 15 000 T (14 763 ton)) at a high cost to the quarry.